Tradisi Songkabala di Kecamatan Sanrobone Kabupaten Takalar (Suatu Kajian Sosio-Kultural) - Rismawati Rismawati (Universitas Islam Negeri Alauddin Makassar, 2014)
Application to the creator to reject and deny the occurrence of disasters, calamities or disasters will befall society has Become a tradition for the people of Sub Sanrobone KabupatenTakalar is Referred to as Songkabala tradition. Songkabala is a form of ritual that serves to resist evil or disaster that would befall mankind. Long before Islam embraced by society Sanrobone, Songkabala tradition has Become the customary rituals of society. at the time Deconstructing the Gowa royal government Sanrobone about abas to XVI . The most interesting part of this study are the elements of trust in the tradition of our ancestors, hereditary, better known by animism. Therefore, the subject matter of this case is to explore and examine the tradition Songkabala specialized in Sub Sanrobone regency Takalar. Concerning the implementation of Islamic tradition and the tradition Songkabala view , the value of local knowledge in implementation of ceremonial traditions and social and cultural impact of traditional practices Songkabala , Become a ticklish very interesting to be studied more deeply and Answered A tradition that Carried people to reject any form of disaster or catastrophe hurricanes, floods, disease, and other natural phenomena do with the process of sending prayers and serving some food needed for a traditional procession Songkabala.